Smad4-expression is decreased in breast cancer tissues: a retrospective study - Dippon Juergen; Buck Miriam B; Stuelten Christina H; Roberts Anita B; Fritz Peter; Knabbe Cornelius (BMC Cancer, 2006)
Abstract Background Although transforming growth factor β (TGF-β) typically inhibits proliferation of epithelial cells, consistent with a tumor suppressor activity, it paradoxically also exhibits pro-metastatic activity in the later stages of carcinogenesis. Since tumors often display altered TGF-β signaling, particularly involving the Smad-pathway, we investigated the role of Smad4-expression in breast cancer. Methods Smad4 expression was investigated by immunohistochemistry in formalin-fixed, paraffin-embedded tissue from 197 samples of primary breast cancer obtained between 1986 and 1998. The prognostic value of Smad4-expression was analyzed. Results Smad4 expression was found to be reduced in lobular and ductal breast carcinoma as compared to surrounding uninvolved lobular and ductal breast epithelia (p < 0.001, n = 50). Smad4-expression correlated positively with expression of TGF-β-receptor I (p < 0.001, n = 197) and TGF-β-receptor II (p < 0.001, n = 197), but showed no significant correlation with tumor size, metastases, nodal status, histological grade, histological type, or estrogen receptor expression. While not achieving statistical significance, there was a trend towards longer survival times in patients with Smad4 negative tumors. Conclusion According to the suggested role of Smad4 as a tumor suppressor we observed that expression of Smad4 is lower in human breast cancer than in surrounding breast epithelium. However, we also observed a trend towards longer survival times in Smad4-negative patients, indicating the complex role of TGF-β signaling in tumor progression.